The portfolio optimization performance during Malaysia’s 2018 General Election by using noncooperative and cooperative game theory approach - Ramadhan bin Ibrahim, Muhammad Akram; Pah, Chin Hee; Islam, Mohd Aminul; Bahaludin, Hafizah (Canadian Center of Science and Education, 2020)
Game theory approach is used in this study that involves two types of games which are noncooperative and cooperative. Noncooperative game is used to get the equilibrium solutions from each payoff matrix. From the solutions, the values then be used as characteristic functions of Shapley value solution concept in cooperative game. In this paper, the sectors are divided into three groups where each sector will have three different stocks for the game. This study used the companies that listed in Bursa Malaysia and the prices of each stock listed in this research obtained from Datastream. The rate of return of stocks are considered as an input to get the payoff from each stock and its coalition sectors. The value of game for each sector is obtained using Shapley value solution concepts formula to find the optimal increase of the returns. The Shapley optimal portfolio, naive diversification portfolio and market portfolio performances have been calculated by using Sharpe ratio. The Shapley optimal portfolio outperformed the naive diversification portfolio and market portfolio in 6 months before and after the GE14.